Sustainable Oil Palm Production in India - Challenges and Opportunities - K. Suresh; R.K. Mathur (Sawit Centre, 2021)
Oil Palm is one of the foremost vegetable oil among the 17 major oils produced and traded in the global edible oil and fat market. Palm oil is an important ingredient for food, feed, fuel and oleo chemical products. The worldwide demand for vegetable oils is increasing; and the future demand for vegetable oil as well as bio-fuel is likely to be met to a major extent by palm oil and palm kernel oil because of its high oil yield. Thus, Oil Palm is considered to be the crop for future. While the crop‘s positive impact on employment and income generation is considerable, oil palm has also been criticized for being a major contributor to deforestation and emissions of greenhouse gases in some countries. However in India, Oil Palm is being promoted purely in agricultural lands, either replacing low value crops or in the land newly brought under irrigation for raising orchards or plantation crops. In India, an area of 28 lakh ha has been identified as potential for oil palm cultivation in 22 States, however only 13 % (3.20 lakh ha) of this has been converted. Oil palm has established as a successful crop in a number of states in the country and many progressive farmers could harvest 30 to 40 tonnes of FFB/ha/year. However, productivity levels of less than 10 tonnes/ha are being recorded by many farmers. In India, oil palm cultivation becomes sustainable by reducing the cultivation cost and improving productivity through better planting materials and efficient resource management, which leads to further area expansion.